The Kindergarten's Headmaster View of the Potential for Learning Loss in Early Childhood Education durung Pandemic COVID-19 - Arzaqi, Roby Naufal; Romadona, Nur Faizah (Indonesian Journal of Early Childhood Education Studies, 2021)
Learning during the COVID19 pandemic through online and home learning presents several challenges and risks of learning loss that have long-term impact. The potential for learning loss can occur during online learning due to several factors due to educational stimuli not working optimally, reduced direct experience gain, differences in skills teaching of teachers in education, etc. This research uses a qualitative approach with a case study design. The participants are two preschool principals and teachers who have been conducting e-learning activities since March 2020 until July 2021. Data collection was carried out through face-to-face interviews and voice notes. Data analysis using thematic analytic. The results of the study revealed that the decline in the quality of online learning faced the risk of potential learning loss in the future. The failure of online learning during this pandemic has created real barriers to some aspects of child development, namely the achievement of aspects of children's cognitive, social and emotional development. Other aspects of development are somewhat difficult for teachers to assess, but it is suspected that there has been a decline due to the limited time spent implementing e-learning. The participation rate of children and parents in online education decreased by 50% from the first semester to the second semester and the number of learning hours was very short. Efforts by schools to prevent the risk of potential learning losses include: blended learning, literacy and numeracy also visiting teacher programs.